Upaya Guru PAI Dalam Meningkatkan Kompetensi Pedagogik di Perguruan Tinggi Era Revolusi Industri 4.0 - Indra Prajoko (Edification Journal : Pendidikan Agama Islam, 2021)
The rapid progress and development of technology and information in the era of the industrial revolution 4.0 has an impact in various fields, such as the impact in the economic, social, political, cultural and educational fields. In learning activities in the world of education, a very important role does not escape from a teacher / educator. Pedagogic competence is one of the concepts designed to be understood and mastered by educators as an important solution in dealing with the problem of Teaching and Learning Activities (KBM). The lack of an educator's innovation about designing and implementing learning activities is still a problem today, especially in the era of the industrial revolution 4.0, it is possible that many educators do not really understand the various media that can be used in the teaching and learning process (KBM) in universities. Besides that, there are still many characteristics of students that are not considered by educators, so that the teaching and learning activities that are carried out are not optimal yet in accordance with the objectives of education. There are various ways that can be held by an educator in improving pedagogical competence itself, such as: participating in educational seminars, participating in PAI subject teacher organizations, increasing willingness by increasing reading and dialogue (discussion) and participating in internal deliberations in the university environmenthigh.